External search for exploration of future discontinuities and trends: Implications from the literature using co-citation and content analysis - Sara Heuschneider; Cornelius Herstatt (Hamburg University of Technology (TUHH), Institute for Technology and Innovation Management (TIM), 2016)
To stay ahead of the competition, firms need to constantly adapt to the changing environment by identifying new opportunities and product innovations. The search for future discontinuities and trends using external knowledge sources enables firms to develop a foresight capability to proactively shape future direction and to improve innovation capacity. Recent open innovation literature discusses external search strategies and their impact on innovation performance. In order to investigate the implications of these findings for external search in the context of foresight, this paper aims to systematically analyze the current focus and intellectual structure of the external search field by means of co-citation and content analysis. Findings indicate a strong focus of the research field on the external search for innovations, e.g. for new product ideas and problem solutions throughout the innovation process. However, it is so far poorly understood how firms can employ external search to detect future discontinuities and trends in the environment. To address this knowledge gap, dimensions of search strategies are derived from the current external search literature and are assessed with respect to their relevance for search in the context of foresight. In the course of the discussion, the breadth and depth of external search as well as the technological, geographical and relational distance of search are found to be relevant dimensions of external search strategies for identifying future developments. The identified dimensions can serve as a starting point to further investigate how firms can benefit from different external search strategies to identify discontinuities and trends in the environment. The paper closes with practical implications and suggestions for further research in this area.
Keywords: 330; external search; corporate foresight; discontinuities; trends; innovation management; search strategies